Atomically thin 2D materials for solution-processable emerging photovoltaics - Stroyuk, Oleksandr; Raievska, Oleksandra; Hauch, Jens; Brabec, Christoph J. (Chemical Communications, 2024)
Atomically thin 2D materials, such as graphene and graphene oxide, covalent organic frameworks, layered carbides, and metal dichalcogenides, reveal a unique variability of electronic and chemical properties, ensuring their prospects in various energy generation, conversion, and storage applications, including light harvesting in emerging photovoltaic (ePV) devices with organic and perovskite absorbers. Having an extremely high surface area, the 2D materials allow a broad variability of the bandgap and interband transition type, conductivity, charge carrier mobility, and work function through mild chemical modifications, external stimuli, or combination with other 2D species into van-der-Waals heterostructures. This review provides an account of the most prominent “selling points” of atomically thin 2D materials as components of ePV solar cells, including highly tunable charge extraction selectivity and work function, structure-directing and stabilizing effects on halide perovskite light absorbers, as well as broad adaptability of 2D materials to solution-based manufacturing of ePV solar cells using sustainable and upscalable printing technologies. A special focus is placed on the large potential of the materials discovery and design of ePV functionalities based on van-der-Waals stacking of atomically thin 2D building blocks, which can open a vast compositional domain of new materials navigable with machine-learning-based accelerated materials screening.
CRIS-Team Scopus Importer:2025-02-04